PENERAPAN MEDIA PERMAINAN KARTU KWARTET UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI MA DAREL HIKMAH PEKANBARU - Oktri Lestari; Jimmi Copriady; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to determine the effect of applying quartet card game media in learning outcomes of students on the subject of Hydrocarbons in the classroom Hikmah X MA Darel Pekanbaru . This type of research is experimental by Design Randomized Control group pretest-posttest. The population is all class Hikmah X Darel Pekanbaru that consists of 7 classes. Sample in this research consisted of two grade obtained after the test of normality and homogeneity, are class X5 and X7. The experimental class was applied with quartet card game media and control class by traditional learning. The data was analysed used t-test with signifcance level (α=0,05) and dk=44, based on the analysis and processing of data obtainable tcount>ttable is 2.82>1.68, this mean that the application of the media can improve the quartet card game student learning outcomes on the subject of Hydrocarbons in the of X class of Darel Hikmah Pekanbaru. The effect of applying media quartet card game for learning outcomes on the subject of hydrocarbons in the classroom Hikmah x MA Darel Pekanbaru 15.3%.Key words :Hydrocarbons, Learning outcomes, Media Quartet Card game,